O caminho das águas na Amazônia: Itinerário da tecnologia naval amazônica e sua proteção jurídica como patrimônio cultural imaterial - Martins, Marco Aurélio de Carvalho (2007)
This research is included in the field of legal protection of the cultural patrimony and aims identify the amazon naval technology as Brazilian immaterial cultural patrimony. This work had as motivator a rule from the SNPH – Amazon Superintendence of Navigation, Ports and Hydro ways, entity that rules the transport of people in the state of Amazonas. It is analyzed the traditional knowledge associated to the amazon naval technology must be considered as cultural patrimony, even if it can not be considered as scientific knowledge. The boats made of wood in Amazon arte part of a social development linked to the waters of the region. Having the biggest hydrographic basin of the world, the rivers and water courses are part of the daily of the amazons relating to their cultural development, what allows that technology of wooden boat construction must be considered as cultural patrimony of the Brazilian society. It is verified how is done the legal protection of the cultural patrimony in a way to protect the technology of boat construction end the wooden boats. It is focused the concern with the defense of this cultural patrimony because of the influence that it has suffered throughout the times, especially because of the attempt of its forced modification. Modify the material of construction of the boats bumps in the meaning that these instruments of transportation have to the amazon society. Even with the possibility of a combination of materials, metal and wood, it is stressed that it is a menace the modification of a cultural patrimony essential to the region, the boats. The legal instrument of protection of this cultural patrimony is the register, instituted by the Decree 3.551/2000, which rules the art. 216 of the Constitution of the Federative Republic of Brazil. Proceedings and its system are analyzed in a way to understand it better, as well as its main characteristics are stressed as it is applied in the understanding that the concern that is pursued is not the defense in a way to not allow its transformation, but to catalog its current situation and follow its development in time. It is concluded that the amazon naval technology is born and blossoms with the regional culture, being a part of its daily relations and being essential to the development of the region. It is observed that these characteristics confirm the idea that this technology is a Brazilian cultural patrimony and must be protected through the register, according to what states the Decree 3.551/2000. Key words: Legal protection of the Cultural Patrimony; Wooden boats; Cultural Patrimony; Constitution of the Federative Republic of Brazil; Register.